COVID-19, extractive industries, and indigenous communities in Canada: Notes towards a political economy research agenda. Issue 3 (July 2020) - Bernauer, Warren; Slowey, Gabrielle
Highlights: The COVID-19 pandemic and associated economic crisis has intensified conflicts between indigenous communities and extractive industries. Struggles over community health, environmental regulations, local benefits, and indigenous rights will likely continue to intensify in the future. It is important for researchers to pay close attention to how these conflicts are affected by the pandemic, in order to help Indigenous communities develop strategies to cope with changes in industry-Indigenous relations. Abstract: As the economic ramifications of the COVID-19 pandemic continue to unfold, it is becoming increasingly apparent that this crisis will have significant and lasting implications for the relationship between extractive industries and Indigenous communities. Using a case study from Canada, this paper examines how the political dynamics of industry-Indigenous relations have changed and speculates about how these dynamics might continue to change in the future. The economic crisis has already intensified political conflicts and struggles between Indigenous peoples and mining, oil, and gas companies. We identify and discuss four points of conflict between Indigenous communities and extractive industries that have become more acute as a result of the current economic crisis. It is important for researchers to pay close attention to how these conflicts are affected by the pandemic, in order to help Indigenous communities develop strategies to cope with changes in industry-Indigenous relations.